African American Identity : Racial and Cultural Dimensions of the Black Experience. - Sullivan, Jas M. (Lexington Books, 2012)
African American Identity: Racial and Cultural Dimensions of the Black Experience, edited by Jas M. Sullivan and Ashraf M. Esmail, is a multidisciplinary exploration of the African American racial identity. The contributors to this volume cover a broad spectrum of disciplines, exploring questions like what is racial identity, how do we quantify it, and what effects do racial identity have on psychological, political, educational, and health-related behavior.